The Relationship between the Party System and Military Intervention in a Transitional Society: The Case of Post-War Greece - Manios, George (My University, 1979)
Tile purpose of this work is. to attempt to demonstrate that the displacement of the civilian political authority in April 1967 by a segment of the Greek Military establishment was the result of the lack of legitimacy of the country's liberal Bourgeois political institutions--in particular the party system. Contemporary Greece is a product of the French Revolution, the Enlightenment and foreign intervention. The small segment of the Greek middle classes that spearheaded the Greek Revolution of 1821 against the Ottoman Turks lacked both ideological cohesion and socio-political legitimacy. The result was that the superimposition of liberal democratic institutions upon the newly "liberated" nation-state whose economic base was in constant fluctuation had adverse affects. Secondly, the inability of the middle classes to destroy or even subordinate the country's quasi-feudal relations, i.e., patronage system, prevented the entrenchment and legitimization of these institutions within the Greek polity. Throughout the country's history military revolts and foreign intervention further contributed to the loss of legitimacy of these institutions, in particular that of the party system. Thus their performance and functions in the political system were impaired. To put it in another way, no political parties were developing along corporate and associational ties capable of becoming the mechanism for the channelling or accommodating the various social groups that were coming into being due to changes in the economic base, i.e., industrialization and urbanization.
As these developments were coming into focus following world War II, the country's military apparatus was experiencing drastic and dramatic change--that is, it was being professionalized, as well as becoming more independent from the political authority. In other words the process of professionalism and the increased autonomy of the military structure contributed to the development of a structural disequilibrium within the Greek political system, hence the military structure acquired unprecedented dominance within Greek society. Furthermore, as this process took place, changes in the economic base allowed the development of new heterogeneous social groups, especially during the early sixties, whose demands could not be marshalled by the existing political parties in view of their patron-client nature. Therefore, the pressures and demands of these social groups led to the disintegration of the party system which in turn created a power vacuum within the political arena, thus facilitating the condition for a component of the Greek Officer Corps to displace the existing civilian political authority and take over the management of the state's affairs on April 21, 1967.
In conclusion, then, this work argues that the Greek political elite should have made some efforts to create viable and legitimate political institutions, i.e., political parties, capable of accommodating new social groups without breaking up and causing political instability for the political system. It is the opinion of this author, that a viable
party system is, at this juncture, a suitable and effective means of developing the Greek political system, as well as preventing future military intrusions.